Studi Komparatif Pemikiran Muhammad Syahrur dan David S. Powers Tentang Hukum Waris Islam - Rifqi, Muhammad Jazil (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2021)
The thought of Islamic law always develops along with changing times, places, and social conditions, and this cannot be separated from the approach applied by every scientist in performing ijtihad. This article reveals a comparative study between Muhammad Syahrur and David S. Powers, who have different backgrounds in interpreting the law, especially inheritance. Syahrur has formal educational experience in the field of engineering. In turn, he studied Islam intensely, while Powers is indeed formally educated in the Islamic world, and although they both use different approaches, they almost have the same view. For Syahrur, there is no absolute specific percentage limit in wills, but the number of wills can be determined by the choices based on the best conditions, in his opinion. Likewise, with inheritance law, the 2: 1 rule for men and women is also not absolute. Under certain conditions, the distribution of property can be 1: 1. Meanwhile, Powers, this testamentary term, is increasingly related to Shahrur's inheritance. It is just that it is intended for heirs whom Ashabul Furudh blocks. Another term that Powers introduced was inheritance ab intestine which was no different from Shahrur's thought. However, it was valid for 2: 1 if the heir was in primary status and 1: 1 if the heir was in the second position.